2022
DOI: 10.1002/pc.27060
|View full text |Cite
|
Sign up to set email alerts
|

Metal/polymer composite cylinders for crash energy absorption applications

Abstract: The crashworthiness performance and the deformation history of glass fiber reinforced epoxy (GFRP) composite over wrapped aluminum (Al) cylinders with induced holes were experimentally studied. Specimens were fabricated using wet wrapping by hand lay-up process and tested under quasi-static axial compression. Crashworthiness indicators that is, the initial peak load F ip À Á , mean crush load (F m ), total absorbed energy (UÞ, specific absorbed energy (SEA), and crush force efficiency (CFE) of the proposed cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
(91 reference statements)
1
14
0
Order By: Relevance
“…According to numerous authors 14,29 , uniaxial quasi-static crush tests do not currently have a standard. Crosshead speed of 10 mm/min was adapted in uniaxial quasi-static crush tests based on many studies in the literature 18,[54][55][56] . Since circular samples absorb more energy and reduce stress concentrations than square or rectangular samples, they were employed to facilitate crushing testing 57 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to numerous authors 14,29 , uniaxial quasi-static crush tests do not currently have a standard. Crosshead speed of 10 mm/min was adapted in uniaxial quasi-static crush tests based on many studies in the literature 18,[54][55][56] . Since circular samples absorb more energy and reduce stress concentrations than square or rectangular samples, they were employed to facilitate crushing testing 57 .…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the intact Al/CFRP tube, of the optimum specimen reduced by 24.32% and SEA is slightly enriched by 0.68%. According to the research done by Alshahrani et al 18 , the criteria that can effectively regulate the performance of crashworthiness and alter the failure mechanism of Al/polymer composite cylinders include the diameter, the number of induced holes, and the number of fiber/epoxy layers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, treated Al-pipes were washed and dried to be used in manufacturing of hybrid composites 32 . This technique was adapted by many investigators [33][34][35][36][37] who confirmed the success of this technique in enhancing the bond between metal and polymer interface.…”
Section: Specimens' Manufacturingmentioning
confidence: 99%